ALDH1 mRNA: presence in human dopamine neurons and decreases in substantia nigra in Parkinson's disease and in the ventral tegmental area in schizophrenia - Dagmar Galter; Silvia Buervenich; Andrea Carmine; Maria Anvret; Lars Olson (Neurobiology of Disease, 2003)
Dopamine (DA) neurons degenerate in Parkinson's disease and dopamine neurotransmission may be affected in psychotic states seen in schizophrenia. Understanding the regulation of enzymes involved in DA metabolism may therefore lead to new treatment strategies for these severe conditions. We investigated mRNA expression of the cytosolic aldehyde dehydrogenase (ALDH1), presumably involved in DA degradation, by in situ hybridization in DA neurons of human postmortem material. Parallel labeling for GAPDH, neuron-specific enolase, tyrosine hydroxylase, dopamine transporter, and dopamine β-hydroxylase was used to ensure suitability of tissue specimen and to identify all dopamine neurons. ALDH1 was found to be expressed highly and specifically in DA cells of both substantia nigra (SN) and the ventral tegmental area (VTA) of controls. A marked reduction of ALDH1 expression was seen in surviving neurons of SN pars compacta but not of those in the VTA in Parkinson's disease. In patients suffering from schizophrenia we found ALDH1 expression at normal levels in DA cells of SN but at significantly reduced levels in those of the VTA. We conclude that ALDH1 is strongly and specifically expressed in human mesencephalic dopamine neurons and that low levels of ALDH1 expression correlate with DA neuron dysfunction in the two investigated human conditions.